2022
DOI: 10.1080/21655979.2021.2019871
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Exosome-delivered BMP-2 and polyaspartic acid promotes tendon bone healing in rotator cuff tear via Smad/RUNX2 signaling pathway

Abstract: Rotator cuff tear is the main form of shoulder joint injury, which seriously affects shoulder joint function. This study aimed to clarify the function and mechanism of exosomes containing polylactic acid (PLA), polylactic acid copolymer and BMP-2 in tendon bone healing of rotator cuff tear. First, CD44 expression in bone marrow mesenchymal stem cells (BMSCs) and CD90 and CD44 in exosomes were analyzed by flow cytometry. Then, stability and targeting identification of exosome-delivered bone morphogenetic protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(67 citation statements)
references
References 40 publications
(38 reference statements)
1
56
0
Order By: Relevance
“…As a peptide growth factor, BMP10 belongs to the BMP family [ 44 ]. BMPs mediate various developmental events and physiological processes in insects and mammals [ 45 , 46 ]. Although the protein structures are similar, each member of the BMP family has a unique amino acid sequence, different distribution characteristics, and diverse physiological functions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a peptide growth factor, BMP10 belongs to the BMP family [ 44 ]. BMPs mediate various developmental events and physiological processes in insects and mammals [ 45 , 46 ]. Although the protein structures are similar, each member of the BMP family has a unique amino acid sequence, different distribution characteristics, and diverse physiological functions [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLA is a biodegradable and recyclable polyester produced from renewable raw materials [ 72 ]. However, synthetic polymers often have a dense structure and small pores, which are not conducive to cell proliferation and adhesion and hinder cell growth [ 73 ].…”
Section: Products Of Tendon and Ligament Reconstruction And Repairmentioning
confidence: 99%
“…Take BMP2, an important regulator of osteogenesis, as an example. Han L. et al (2022) reported that BMP2 in BMSC-derived exosomes could promote tendon bone healing in rotator cuff tear by activating Smad/RUNX2 signaling pathway. Conversely, in another study, exosomes derived from MSCs overexpressing BMP2 did not contain BMP2 protein, and the function of promoting bone regeneration was possibly due to the changes of exosomal miRNA composition ( Huang et al, 2020 ).…”
Section: Osteogenic Cargos In Exosomesmentioning
confidence: 99%